Nerve-Sparing Radical Hysterectomy: Kobayashi's Method - Hiroyuki Yoshikawa (The Surgery Journal, 2021)
After Prof. S. Okabayashi introduced Okabayashi Operation in 1921, several surgeons introduced numerous improvements in Japan. One of them is so-called the Tokyo Method which was improved and revised by Dr. Kyusaku Ogino (1950), Prof. Takashi Kobayashi, University of Tokyo (1961, 1970), and Prof. Shoichi Sakamoto, University of Tokyo (1981). The nerve-sparing radical hysterectomy without sacrificing radicality was introduced in 19611 and improved in 1970 by Prof. Kobayashi.2 The autonomic nerve pathway including hypogastric nerve (sympathetic nerve), pelvic splanchnic nerve (parasympathetic nerve), and pelvic nerve plexus as a junction of the two nerves and the branch of the plexus to the bladder (vesical nerve branch) are preserved except in advanced cases. He divided the process of nerve-sparing surgery into four steps for separating the autonomic nerve pathway from adjacent tissues along the pathway consisting of cardinal, sacrouterine, rectouterine/vaginal, and vesicouterine ligaments. The first step is separation of the cardinal ligament (deep uterine vessels) from the pelvic splanchnic nerve. The second step is separation of the medial side of severed cardinal ligament from the pelvic nerve plexus. The first and second steps are performed in the lateral side of the autonomic nerve system. The third step is separation of sacrouterine and rectouterine/vaginal ligaments from hypogastric nerve and pelvic nerve plexus. The third step is necessary for achieving high radicality, namely, for severing the sacrouterine and rectouterine/vaginal ligaments near the rectum without damage to the pelvic nerve plexus. The fourth step is separation of paravaginal tissues and posterior (deep) layer of the vesicouterine ligament from the vesical nerve branches of the plexus. The third and fourth steps are performed in the medial side of the autonomic nerve system.